2015
DOI: 10.5152/npa.2015.8777
|View full text |Cite
|
Sign up to set email alerts
|

Attentional Bias and Training in Social Anxiety Disorder

Abstract: Cognitive behavioral therapy (CBT) is one of the most effective treatment modalities for social anxiety disorder (SAD), showing a high level of clinical evidence supporting its effectiveness. On the other hand, lack of the desired benefit from this treatment in some patients causes continuation of the search for new techniques. Recent research studies have focused on attentional bias and attention training in SAD. Attention processes in SAD have been a major target of interest and investigation since the intro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
3
0
2
Order By: Relevance
“…These effects should be investigated in help-seeking SAD samples, and if found to be relevant, attentional guidance and practice could be used to alter these biases and any negative outcomes associated with them. Attentional training as an adjunct to more established psychosocial interventions has already shown some promise (Fistikci et al, 2015) and the findings of the current study may lead to improvements in this approach.…”
Section: Limitations Future Directions and Clinical Implicationsmentioning
confidence: 81%
See 1 more Smart Citation
“…These effects should be investigated in help-seeking SAD samples, and if found to be relevant, attentional guidance and practice could be used to alter these biases and any negative outcomes associated with them. Attentional training as an adjunct to more established psychosocial interventions has already shown some promise (Fistikci et al, 2015) and the findings of the current study may lead to improvements in this approach.…”
Section: Limitations Future Directions and Clinical Implicationsmentioning
confidence: 81%
“…Empirical research and cognitive models place emphases on atypical attentional processes in the disorder (Bögels & Mansell, 2004;Clark & Wells, 1995). In addition, recent therapeutic interventions for the condition have focused on modifying attentional processes to reduce anxiety, with some success (Davidson et al, 2004;Fistikci, Saatcioğlu, Keyvan, Kalkan, & Topçuoğlu, 2015).…”
mentioning
confidence: 99%
“…Cognitive models of emotional disorders have been supported by numerous studies that have shown that attentional bias is related to social anxiety levels in children and adolescents (Puliafico and Kendall, 2006; Roy et al, 2008; Hankin et al, 2010; Dudeney et al, 2015), as well as in adults (Roberts et al, 2010; Morrison and Heimberg, 2013; Fistikci et al, 2015; Wong and Rapee, 2016). For example, Shechner et al (2013) examined eye movement in children and adolescents aged 8 – 17 and identified that those with anxiety disorders had attentional bias to threat.…”
Section: Introductionmentioning
confidence: 99%
“…Alguns estudos indicam que indivíduos com TAS geralmente apresentam maior tempo de resposta em nomear cores de palavras que representam ameaça social do que palavras neutras em relação a indivíduos saudáveis, além de apresentar um viés atencional para ameaça avaliado por outros paradigmas experimentais (Becker, Rinck, Margrad, & Roth;Calamaras, Tone, & Anderson, 2012;Fistikci, Saatcioglu, Keyvan, Kalka, & Topçuoglu, 2015;Grant & Beck, 2006;Nortje & Posthumus, 2012 relacionada também a uma mudança no processamento de estímulos sociais.…”
Section: Viés Atencionalunclassified
“…Assim, a resposta ao teste pode estar relacionada tanto a um viés para ameaça, quanto a tentativas de inibição do significado das palavras do teste (Amir & Bomyea, 2010;Baños,Quero & Botella, 2004;Fistikci, Saatcioglu, Keyvan, Kalka, & Topçuoglu, 2015 (Baños, Quero & Botella, 2004;Holle et al,1997;Quero, Baños & Botella., 2000). Assim, a literatura indica que a presença de viés parece ser mais comumente observada quando: 1) utiliza-se o formato de listas; e 2) emprega-se a apresentação conjunta de palavras de uma mesma categoria (apresentação em blocos de acordo com a valência), seja no formato computadorizado ou em listas (Holle et al,1997;Quero, Baños & Botella., 2000 Deve-se destacar ainda a limitação relacionada ao viés do pesquisador, que atuou como avaliador e também terapeuta da presente pesquisa.…”
Section: Pós-testeunclassified